Dynamic optimization of intersatellite link assignment based on reinforcement learning. (February 2022) - Ren, Weiwu; Zhu, Jialin; Qi, Hui; Cong, Ligang; Di, Xiaoqiang
Intersatellite links can reduce the dependence of satellite communication systems on ground networks, reduce the number of ground gateways, and reduce the complexity and investment of ground networks, which are important future trends in satellite development. Intersatellite links are dynamic over time, and different intersatellite topologies have a great impact on satellite network performance. To improve the overall performance of satellite networks, a satellite link assignment optimization algorithm based on reinforcement learning is proposed in this article. Different from the swarm intelligence method in principle, this algorithm models the combinatorial optimization problem of links as the optimal sequence decision problem of a series of link selection actions. Realistic constraints such as intersatellite visibility, network connectivity, and number of antenna beams are regarded as fully observable environmental factors. The agent selects the link according to the decision, and the selection action utility affects the next selection decision. After a finite number of iterations, the optimal link assignment scheme with minimum link delay is achieved. The simulation results show that in 8 or 12 satellite network systems, compared with the original topology, the topology calculated by this method has better network delay and smaller delay variance.